USE OF FAKE VEHICLE NUMBER PLATES REVIEWED FROM A CRIMINOLOGICAL ASPECT - Lubis, Anju Mohammad Perwira (Inspiring Law Journal, 2025)
Motor vehicle license plates (TNKB) are official identification issued by the police to legalize the use of vehicles on the highway. However, the practice of using fake vehicle license plates is increasingly widespread, especially in big cities such as Medan. This violation is committed for various reasons, such as avoiding odd-even rules, not paying taxes, or using unofficial vehicles (bodong). Forgery of license plates and supporting documents such as STNK (Vehicle Registration Certificate) often occurs, even sold openly through social media. Although there are laws and regulations governing the use of TNKB, such as Law Number 22 of 2009 concerning Traffic and Road Transportation, as well as the criminal sanctions imposed, this violation continues to occur. This study aims to analyze the use of fake vehicle license plates from a criminological aspect, with a focus on the causal factors, impacts, and efforts to overcome them. Criminology as a science that studies crime and its causes has an important role in understanding this phenomenon and formulating solutions to reduce these illegal practices. Through a criminological approach, this research is expected to contribute to increasing public awareness of the importance of using official TNKB and encourage more effective law enforcement.